2010
DOI: 10.1093/humrep/dep476
|View full text |Cite
|
Sign up to set email alerts
|

What next for preimplantation genetic screening (PGS)? A position statement from the ESHRE PGD Consortium steering committee 

Abstract: Since 2004, there have been 11 randomized controlled trials (RCTs) mainly for advanced maternal age (AMA), which have shown no benefit of performing preimplantation genetic screening (PGS). Ten of the RCTs have been performed at the cleavage stage and one at the blastocyst stage. It is probable that the high levels of chromosomal mosaicism at cleavage stages, which may result in the tested cell not being representative of the embryo, and the inability to examine all of the chromosomes using fluorescence in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(84 citation statements)
references
References 23 publications
0
82
0
2
Order By: Relevance
“…Other studies later reaffirmed the results reported by Mastenbroek et al [3][4][5][6]. Professional organizations followed by unequivocally concluding that PGS, at current practice levels, did not improve clinical IVF outcomes [7][8][9].…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Other studies later reaffirmed the results reported by Mastenbroek et al [3][4][5][6]. Professional organizations followed by unequivocally concluding that PGS, at current practice levels, did not improve clinical IVF outcomes [7][8][9].…”
Section: Introductionmentioning
confidence: 72%
“…Published reviews in the literature are confirmatory [6,33,34]. PGS utilization to improve pregnancy and miscarriage rates, based on currently available data [1,2,7,9,29,30,35,36] should, therefore, only occur under study conditions, and with appropriate informed consents.…”
Section: The Current Status Of Pgsmentioning
confidence: 90%
See 2 more Smart Citations
“…Following this report, other studies followed failing to demonstrate a benefit of PGS in terms of pregnancy outcome. Subsequently, multiple major professional societies including the American Society for Reproductive Medicine (ASRM), the American College of Obstetrics and Gynecology (ACOG), and the European Society of Human Reproduction and Embryology (ESHRE) all released formal opinions discouraging the general use of PGS [12][13][14].…”
Section: Pgs: the Early Daysmentioning
confidence: 99%